Circular RNA hsa_circ_0001380 in peripheral blood as a potential diagnostic biomarker for active pulmonary tuberculosis - Luo, Hou‑Long; Peng, Ying; Luo, Hong; Zhang, Jun‑Ai; Liu, Gan‑Bin; Xu, Huan; Huang, Gui‑Xian; Sun, Yin‑Fu; Huang, Ji; Zheng, Bi‑Ying; Zhong, Ji‑Xin; Xu, Jun‑Fa (Molecular medicine reports, 2020)
Numerous studies have suggested that circular RNAs (circRNAs), a type of non‑coding RNA lacking 5'‑caps and 3'‑poly(A) tails, are involved in the biological processes of various human diseases. However, little is known about their functions and diagnostic value in active pulmonary tuberculosis (APTB). The aim of the present study was to examine whether hsa_circ_0001380 is able to serve as a diagnostic biomarker for patients with APTB. The expression level of hsa_circ_0001380 was detected in the peripheral blood of 32 patients with APTB and 31 healthy volunteers by reverse transcription‑quantitative PCR. The functional prediction of hsa_circ_0001380 was performed in silico. RNase R was used to detect the stability of hsa_circ_0001380. Finally, the diagnostic value of hsa_circ_0001380 was evaluated by receiver operating characteristic (ROC) curve analysis. The results showed that hsa_circ_0001380 was significantly downregulated in the peripheral blood of patients with APTB. In addition, hsa_circ_0001380 was found to be resistant to RNase R treatment. Moreover, four N6‑adenosine methylation modification sites and two potential microRNA binding sites were predicted in silico. Importantly, the area under the ROC curve was 0.9502, which suggested that hsa_circ_0001380 may act as a diagnostic biomarker for APTB. Taken together, the results indicated that circRNA hsa_circ_0001380 was downregulated in the peripheral blood of patients with APTB, and could serve as a diagnostic biomarker.